Efficacy and safety of tisotumab vedotin in previously treated recurrent or metastatic cervical cancer (innovaTV 204/GOG-3023/ENGOT-cx6): a multicentre, open-label, single-arm, phase 2 study. Issue 5 (May 2021) - Coleman, Robert L; Lorusso, Domenica; Gennigens, Christine; González-Martín, Antonio; Randall, Leslie; Cibula, David; Lund, Bente; Woelber, Linn; Pignata, Sandro; Forget, Frederic; Redondo, Andrés; Vindeløv, Signe Diness; et al.
Summary: Background: Few effective second-line treatments exist for women with recurrent or metastatic cervical cancer. Accordingly, we aimed to evaluate the efficacy and safety of tisotumab vedotin, a tissue factor-directed antibody–drug conjugate, in this patient population. Methods: This multicentre, open-label, single-arm, phase 2 study was done across 35 academic centres, hospitals, and community practices in Europe and the USA. The study included patients aged 18 years or older who had recurrent or metastatic squamous cell, adenocarcinoma, or adenosquamous cervical cancer; disease progression on or after doublet chemotherapy with bevacizumab (if eligible by local standards); who had received two or fewer previous systemic regimens for recurrent or metastatic disease; had measurable disease based on Response Evaluation Criteria in Solid Tumors (RECIST; version 1.1); and had an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients received 2·0 mg/kg (up to a maximum of 200 mg) tisotumab vedotin intravenously once every 3 weeks until disease progression (determined by the independent review committee) or unacceptable toxicity. The primary endpoint was confirmed objective response rate based on RECIST (version 1.1), as assessed by the independent review committee. Activity and safety analyses were done in patients who received at least one dose of the drug. This study is ongoing with recruitment completed and is registered with ClinicalTrials.gov, NCT03438396 . Findings: 102 patients were enrolled between June 12, 2018, and April 11, 2019; 101 patients received at least one dose of tisotumab vedotin. Median follow-up at the time of analysis was 10·0 months (IQR 6·1–13·0). The confirmed objective response rate was 24% (95% CI 16–33), with seven (7%) complete responses and 17 (17%) partial responses. The most common treatment-related adverse events included alopecia (38 [38%] of 101 patients), epistaxis (30 [30%]), nausea (27 [27%]), conjunctivitis (26 [26%]), fatigue (26 [26%]), and dry eye (23 [23%]). Grade 3 or worse treatment-related adverse events were reported in 28 (28%) patients and included neutropenia (three [3%] patients), fatigue (two [2%]), ulcerative keratitis (two [2%]), and peripheral neuropathies (two [2%] each with sensory, motor, sensorimotor, and neuropathy peripheral). Serious treatment-related adverse events occurred in 13 (13%) patients, the most common of which included peripheral sensorimotor neuropathy (two [2%] patients) and pyrexia (two [2%]). One death due to septic shock was considered by the investigator to be related to therapy. Three deaths unrelated to treatment were reported, including one case of ileus and two unknown causes. Interpretation: Tisotumab vedotin showed clinically meaningful and durable antitumour activity with a manageable and tolerable safety profile in women with previously treated recurrent or metastatic cervical cancer. Given the poor prognosis for this patient population and the low activity of current therapies in this setting, tisotumab vedotin, if approved, would represent a new treatment for women with recurrent or metastatic cervical cancer. Funding: Genmab, Seagen, Gynaecologic Oncology Group, and European Network of Gynaecological Oncological Trial Groups.